Effects of forage feeding on rumen fermentation, plasma metabolites, and hormones in Holstein calves during pre- and postweaning periods1 - Takemura, Kei; Shingu, Hiroyuki; Mizuguchi, Hitoshi; Kim, Yo-Han; Sato, Shigeru; Kushibiki, Shiro (Journal of animal science, 2019)
Abstract Recent studies have suggested that the amount of forage intake by calves around the time of weaning could affect ruminal pH levels. Several studies have also proposed that subacute ruminal acidosis in mature cows is a risk factor for various metabolic disorders and production diseases. In this study, we examined the effects of forage feeding on ruminal pH, ruminal fermentation, rumen lipopolysaccharide (LPS) concentration, plasma metabolites, and hormonal concentrations in calves during pre- and postweaning periods. Sixteen male Holstein calves were used. At 7 wk of age, calves were randomly assigned to one of two dietary treatments: calves in the HAY group (n = 8) were fed starter with forage, and those in the CON group (n = 8) were fed starter without any forage. All calves were weaned at 8 wk of age. The amounts of starter and mixed hay were gradually increased until the end of the experiment (age, 11 wk). Ruminal pH was measured continuously every 10 min using an indwelling sensor. Rumen fluid and peripheral blood samples were obtained prior to morning feedings at −1, 0, 1, and 3 wk after weaning. Compared with the HAY group, in the CON group, the average daily ruminal pH was lower (P < 0.05) and the duration of ruminal pH values below 5.6 was longer (P < 0.05). Regarding ruminal VFA profiles, compared with the HAY group, the CON group had lower (P < 0.05) acetate to propionate ratios at 1 and 3 wk after weaning. Rumen LPS concentrations tended to be higher (P < 0.1) in the CON group than in the HAY group; however, concentrations of LPS-binding protein, haptoglobin, and serum amyloid A in the peripheral blood did not differ significantly. Plasma aspartate aminotransferase and alkaline phosphatase levels were markedly higher (P < 0.05) in the CON group than in the HAY group at 1 and 3 wk after weaning. There was a linear decrease in plasma growth hormone (GH) levels in the CON group after the start of the experiment, and its concentrations were lower (P < 0.05) in the CON group than in the HAY group at 0 and 3 wk after weaning. The results indicated that forage provision during pre- and postweaning periods helped prevent decrease in ruminal pH, change in ruminal fermentation, and liver alteration, and helped maintain plasma GH levels, which suggests that calves around the time of weaning need forage intake with starter to maintain proper metabolic and hormonal functions.